2023
DOI: 10.1002/hpja.758
|View full text |Cite
|
Sign up to set email alerts
|

Equipping fathers to support distressed mothers: What do mothers want fathers to know and do?

Abstract: Issue AddressedUp to one in five new mothers experience depression or anxiety, and their partners are often the first line of social and practical support. However, many fathers are unprepared for their role as support person. The SMS4dads program (www.sms4dads.com) provides text‐based support to new fathers but lacks specific messages addressing maternal mental distress.MethodsA mixed methods process engaged mothers with lived experience of perinatal mental distress to identify message content for co‐designin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 52 publications
1
4
0
Order By: Relevance
“…Central to the improvements suggested by healthcare professionals, is the recognition that family healthcare services in the perinatal period are focused on women and children and can be improved by including the perspective and roles of fathers and partners when services are designed and implemented. This is consistent with existing calls for more father‐inclusive practice among clinicians and researchers 2,3 …”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Central to the improvements suggested by healthcare professionals, is the recognition that family healthcare services in the perinatal period are focused on women and children and can be improved by including the perspective and roles of fathers and partners when services are designed and implemented. This is consistent with existing calls for more father‐inclusive practice among clinicians and researchers 2,3 …”
Section: Discussionsupporting
confidence: 89%
“…This is consistent with existing calls for more father-inclusive practice among clinicians and researchers. 2,3 Given the influence of intersectionality in shaping culturally diverse fathers' experiences, it is necessary to ensure that training for healthcare professionals recognises the influence of culture on fathering. This suggests that when designing father-inclusive training programs, resource developers need to consider the experiences of culturally diverse fathers explicitly, otherwise their perspectives and needs may be lost among the perspectives of the majority cultural group.…”
Section: Key Implications For Policy and Practicementioning
confidence: 99%
See 2 more Smart Citations
“…More specifically, prior work has found that mothers not only show considerable emotional and physiological reactivity to family conflict (Sears et al, 2016; Sturge-Apple et al, 2009), but mothers also tend to operate as mediators of relationship discord within the romantic and parent–child relationships (Heaton & Blake, 1999; Li et al, 2020; Vuchinich et al, 1988). Thus, the competing demands of having to monitor the emotional integrity of the family may be particularly taxing to mothers of young children who are also responsible for many of the primary caregiving responsibilities within U.S. samples (Fletcher et al, 2023; Schoppe-Sullivan et al, 2013).…”
Section: Discussionmentioning
confidence: 99%